Kon̈nen Produktionsentscheidungen als Investitionsentscheidungen modelliert werden? - Stefan Mann; Gabriele Mack; Ali Ferjani (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
– Interviews with Swiss farmers lead to the hypotheses that production decisions, also in crop growing, are not made annually, but similarly to investment decisions in the long run. This hypothesis is backed by non-parametric time-series analysis for Switzerland and Germany. This creates a theoretical basis for combining Positive Mathematical Programming with flexibility constraints in optimization models. Results of the forecasting model SILAS show that forecasting quality is improved through this approach.
Keywords: 330